PERAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMAN 9 MATARAM - Wulandari; Moh; Syamsul Hadi; Bagdawansyah Alqadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on the role of the principal in implementing the Merdeka Curriculum at SMAN 9 Mataram, with two main research questions: (1) How is the principal's role in implementing the Merdeka Curriculum at SMAN 9 Mataram? and (2) What are the supporting and inhibiting factors in the implementation of the Merdeka Curriculum? This qualitative descriptive research collected data through observation, interviews, and documentation, involving the principal, vice principals of curriculum, facilities and infrastructure, student affairs, and teachers. The data were analyzed using three stages: data reduction, data display, and conclusion drawing. Based on the findings: (1) The principal plays several roles in implementing the Merdeka Curriculum, including as an educator who guides, mentors, and evaluates teachers; as a leader who makes decisions and shows strong commitment; as a manager who oversees curriculum planning, implementation, organization, and evaluation; as a supervisor who monitors and assesses teacher performance; and as a motivator who continuously encourages teachers to stay enthusiastic in supporting the success of the curriculum. (2) The supporting factors include the availability of adequate facilities, good coordination, and a reward and punishment system, while the inhibiting factors involve teachers who lack understanding and digital literacy, which hinders innovation and alignment with the Merdeka Curriculum.